A Digital Empire in the Making: China's Outbound Digital Platforms - Keane, Michael; Yu, Haiqing (USC ANNENBERG PRESS, 2019)
In this article, we use the example of e-commerce giant Alibaba and its outbound activities in the Asia-Pacific to illustrate how China’s digital platforms have become part of a “digital empire in the making.” The article examines how this emergent digital empire is a manifestation of “going out,” a term used by the Chinese government to rally the private sector (particularly platform capitalists) to internationalize, and how digital champions such as Alibaba have responded to and embraced an outward-bound strategy. Though the Asia-Pacific represents an important region for Chinese economic security, especially when one considers the established business interests there, extension of Chinese influence to central Asia conjures up a different kind of weida fuxing (great rejuvenation), one that evokes a great historical past—namely, the Chinese empire. Accordingly, we speculate on how digital technologies, platforms, and business mergers will facilitate Chinese influence along the digital Silk Roads.